The orchardist : a novel - Coplin, Amanda (New York : Harper, 2012)
At the turn of the 20th century in a rural stretch of the Pacific Northwest, a gentle solitary orchardist, Talmadge, tends to apples and apricots. Then two feral, pregnant girls and armed gunmen set Talmadge on an irrevocable course not only to save and protect but to reconcile the ghosts of his own troubled past.
Keywords: Fruit growers -- Fiction; Orchards -- Northwest, Pacific -- Fiction; Pregnant teenagers -- Fiction; Families -- Fiction